HUBUNGAN ATRIBUT FUNCTION, FEATURE DAN BENEFIT TERHADAP PENGGUNAAN OBAT TRADISIONAL DI KOTA KUPANG - Novi Winda Lutsina; Agustinus Dian Setiawan (Fakultas Farmasi Universitas Setia Budi, 2025)
The use of traditional medicine depends on the uniqueness of the product as seen from the attributes it has. Product attributes consist of three types, namely features, functions, and benefits. This type of research is quantitative with a correlative design using linear regression analysis at pharmacies in 6 districts of Kupang City. The results of the study showed that the function, feature, and benefit attributes together had a significant relationship to the satisfaction of using traditional medicine (F = 0.001 <0.05), while partially the function attribute did not have a significant relationship (t = 0.56 > 0.05), the feature attribute had a significant relationship (t = 0.001 <0.05), and the benefit attribute had a significant relationship (t = 0.001 <0.05) to satisfaction.